2015
DOI: 10.1002/adsc.201500334
|View full text |Cite
|
Sign up to set email alerts
|

Palladium‐Catalyzed Alkene Carboamination Reactions of Electron‐Poor Nitrogen Nucleophiles

Abstract: Modified reaction conditions that facilitate Pd-catalyzed alkene carboamination reactions of electron-deficient nitrogen nucleophiles are reported. Pent-4-enylamine derivatives bearing N-tosyl or N-trifluoroacetyl groups are coupled with aryl triflates to afford substituted pyrrolidines in good yield. These reactions proceed via a mechanism involving anti-aminopalladation of the alkene, which differs from previously reported analogous reactions of N-aryl and N-boc pentenylamines. The application of these condi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 40 publications
0
19
0
Order By: Relevance
“…For example, Peterson and Wolfe demonstrated that N-tosyl-or N-trifluoroacetyl-protected aminoalkene substrates (94)w ere transformed into substitutedp yrrolidines (95)i n good yields when conditions that favored anti-aminopalladation were employed (Scheme 33). [44] The chemical yields of these reactions were generally good;however,the diastereoselectivities were only moderate and, in most cases, lower than those that were obtained in reactions of similars ubstrates that proceeded through a syn-aminopalladation pathway.…”
Section: Reactionsbetween Aryl/alkenyl Electrophiles and Alkenes Thatmentioning
confidence: 89%
“…For example, Peterson and Wolfe demonstrated that N-tosyl-or N-trifluoroacetyl-protected aminoalkene substrates (94)w ere transformed into substitutedp yrrolidines (95)i n good yields when conditions that favored anti-aminopalladation were employed (Scheme 33). [44] The chemical yields of these reactions were generally good;however,the diastereoselectivities were only moderate and, in most cases, lower than those that were obtained in reactions of similars ubstrates that proceeded through a syn-aminopalladation pathway.…”
Section: Reactionsbetween Aryl/alkenyl Electrophiles and Alkenes Thatmentioning
confidence: 89%
“…Next, we investigated α‐substituted allyl amines (Scheme , C ) . This class of substrates required the use of cesium triflate as additive to ensure high conversions . Substitution by a methyl group furnished the desired imidazolidine 18 in high yield, albeit in low diastereoselectivity.…”
Section: Methodsmentioning
confidence: 99%
“…[14] This class of substrates required the use of cesium triflate as additive to ensure high conversions. [15] Substitution by am ethyl group furnished the desired imida-zolidine 18 in high yield, albeit in low diastereoselectivity.A bis-allylic amine delivered product 19 in good yield and diastereoselectivity.B icyclic and tricyclic imidazolidines 20, 21,a nd 22 were formed in high diastereoselectivity.T hese results highlight the fast access to complex structures with control on up to four stereocenters in asingle step.…”
Section: Angewandte Chemiementioning
confidence: 99%
“…Electron-rich DavePhos was not efficient (entry 12). Regarding bidentate phosphines,B INAP was not competent, DPE-Phos yielded 90 %o f4,a nd closely related XANTPhos only 58 %( entries [13][14][15]. Switching to cesium hydrogen carbonate as base reduced the yield significantly but still afforded ar easonable amount of 4,w hile potassium carbonate provided 89 %o ft he desired imidazolidine (entries 16 and 17).…”
mentioning
confidence: 99%